Tau propagation is dependent on the genetic background of mouse strains. Issue 2 (23rd February 2022) - Dujardin, Simon; Fernandes, Analiese; Bannon, Riley; Commins, Caitlin; De Los Santos, Mark; Kamath, Tarun V.; Hayashi, Mansuo; Hyman, Bradley T.
Abstract: Progressive cognitive decline in Alzheimer's disease correlates closely with the spread of tau protein aggregation across neural networks of the cortical mantle. We tested the hypothesis that heritable factors may influence the rate of propagation of tau pathology across brain regions in a model system, taking advantage of well-defined genetically diverse background strains in mice. We virally expressed human tau locally in the hippocampus and the entorhinal cortex neurons and monitored the cell-to-cell tau protein spread by immunolabelling. Interestingly, some strains showed more tau spreading than others while tau misfolding accumulated at the same rate in all tested mouse strains. Genetic factors may contribute to tau pathology progression across brain networks, which could help refine mechanisms underlying tau cell-to-cell transfer and accumulation, and potentially provide targets for understanding patient-to-patient variability in the rate of disease progression in Alzheimer's disease. Abstract : Dujardin et al . report that when human tau is expressed locally in the brain of mice with diverse genetic backgrounds, some backgrounds show more tau cell-to-cell spreading than others while tau misfolding accumulated at the same rate underpinning that genetic factors may contribute to tau pathology progression across brain networks. Graphical Abstract: Graphical Abstract